Implications Of Removable Partial Denture Treatment Using An Abutment Tooth Following Root Canal Treatment And Jacket Crown Restoration: A Case Report - Aulia Salsabila Agata; Retno Sari (International Journal of Health Engineering and Technology, 2026)
Partial tooth loss remains a prevalent condition in Indonesia, with a prevalence rate of 51.4% based on data from the Basic Health Research (Riskesdas) of 2018. One of the most widely used treatment options for tooth loss is the fabrication of acrylic resin removable partial dentures (RPD). The advantages of acrylic resin RPDs include their cost-effectiveness and ease of fabrication. The success of an RPD is greatly influenced by the condition of the mucosal tissues and abutment teeth as supporting structures. A 23-year-old female patient presented with discomfort during eating following the extraction of residual roots from the posterior mandibular and maxillary teeth. The patient had previously undergone root canal treatment and crown placement on the mandibular left posterior tooth. The patient wants a removable denture to be made. The selection of clasp type for an abutment tooth that has undergone root canal treatment and been restored with a jacket crown requires careful consideration of the periodontal condition, undercut depth, and functional load distribution, so that the retention of the prosthesis can be adequately maintained. This case demonstrates that a tooth that has undergone root canal treatment and been restored with a jacket crown can serve as an effective abutment for a removable partial denture, provided that a comprehensive evaluation of the supporting tissues and appropriate design planning are carried out.